A multiphysics evaluation of the rejuvenator effects on aged asphalt using molecular dynamics simulations. (20th June 2020) - Cui, Bingyan; Gu, Xingyu; Hu, Dongliang; Dong, Qiao
Abstract: The rejuvenator effects on aged asphalt are easily influenced by multiple physical conditions such as ultraviolet irradiation, overheating and water exposure. In this study, a multiphysics evaluation of the rejuvenator effects on aged asphalt was conducted using molecular dynamics (MD) simulations. Different rejuvenator dosages were added to the aged asphalt model to observe the changes in the microscopic properties. Then, water and temperature fields were considered in the simulation to investigate their individual and coupled effects on rejuvenators. The results showed that the effect of rejuvenators in aged asphalt on weakening the rutting resistance was greater than that of improving the cracking resistance. Regarding the microstructure of asphalt, the colloidal structure still could not be fully restored, although adding rejuvenators could help mitigate the self-aggregation of asphaltenes. In addition, it was discovered that the increase in rejuvenators improved the moisture damage resistance of aged asphalt, which had better adhesion with Al2 O3 than SiO2 . The rejuvenators could diffuse 2–3 times faster at hot-mix temperatures than warm-mix temperatures. Additionally, under high temperatures, rejuvenators with low dosages had higher diffusion coefficients compared to that of high dosages of rejuvenators. For the multiphysics coupled effects of temperature and water, both water and high temperatures were found to have negative effects on the work of adhesion between the asphalt and aggregates, where the effect of the water was more significant compared with that of high temperatures.